2017
DOI: 10.1007/s11745-017-4247-0
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fermented by Lactic Acid Bacteria Enhances the Absorption of Dietary Sphingomyelin in Rats

Abstract: Supplementation with sphingomyelin has been reported to prevent disease and maintain good health. However, intact sphingomyelin and ceramides are poorly absorbed compared with glycerolipids. Therefore, if the bioavailability of dietary sphingomyelin can be increased, supplementation would be more effective at lower doses. The aim of this study in rats was to evaluate the effect of fermented milk on the bioavailability of dietary sphingomyelin in rats. After the rats had fasted for 15 h, test solutions were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…These values are in accordance with reported values for the composition of MPL and SPL. Specifically, the composition of the Fonterra MPL was previously reported to contain 33.68, 23.91, 10.12, and 32.29 g of PC, PE, PI, and SM, respectively, per 100 g of PL (Morifuji et al, 2017). Furthermore, the SPL-LUV composition is in accordance with soy lecithin values reported in the literature.…”
Section: Characterization Of Milk and Soy Phospholipid Liposomes And Inflammation In 3t3-l1 Adipocytessupporting
confidence: 83%
“…These values are in accordance with reported values for the composition of MPL and SPL. Specifically, the composition of the Fonterra MPL was previously reported to contain 33.68, 23.91, 10.12, and 32.29 g of PC, PE, PI, and SM, respectively, per 100 g of PL (Morifuji et al, 2017). Furthermore, the SPL-LUV composition is in accordance with soy lecithin values reported in the literature.…”
Section: Characterization Of Milk and Soy Phospholipid Liposomes And Inflammation In 3t3-l1 Adipocytessupporting
confidence: 83%
“…It has been reported that a milk fermentation containing SM and two LAB (L. delbrueckii subsp. bulgaricus 2038 and Streptococcus thermophilus 1131) increases the absorption of this phospholipid in murine models [90]. As previously discussed, SM is regarded for its function in regulating inflammation [105], promoting neurodevelopment and cognitive function [106,107], and improving the skin barrier function [108], among others.…”
Section: Nutrient Absorption Mucosal Immunity and Gut Barrier Functionmentioning
confidence: 97%
“…In this study, we show that unique sphingoid bases derived from CAEP, including d19:3 and d16:1, can be absorbed from the intestine; these sphingoid bases were found only in the lymph after administration of CAEP. Studies have shown that d16:1, which is a major sphingoid base in bovine milk, is a suitable marker for evaluating lymphatic absorption of dietary milk sphingomyelin (11,37).…”
Section: Discussionmentioning
confidence: 99%